Evaluating Perceived Entrepreneurial Skills for Self-Reliance among Business Education Undergraduates in South-Western States’ Universities in Nigeria - Aina, M. Adebayo; Oyerinde, D. Oluseyi; Onajite, O. Godwin; Falade, C. Adekunbi (Mediterranean Journal of Social Sciences, 2020)
Unemployment has become a household name among graduates in Nigeria. It is more worrisome when business education graduates are conspicuously found among the unemployed graduates roaming around the streets. This study therefore evaluated the extent of possession of communication, financial management and failure management skills for self-reliance among business education undergraduate students in south-western states. The survey research design was adopted. The population of the study consisted of 630 final year Business Education students in all the four public universities offering Business Education programme. The sample of the study consisted of 150 respondents, representing 24%, which was selected through proportionate sampling technique. A self-designed questionnaire titled “Questionnaire on Evaluating Entrepreneurial Skills for Self-Reliance “(QEESSR) with 35 items was developed to elicit responses on the three research questions raised for the study. The instrument was validated by two Business Education experts and one Test expert. The split half method was used to determine the reliability of the instrument and the data collected were subjected to Pearson Product Moment Correlation formula and yielded a coefficient of 0.72. The study concludes that Business Education students highly possessed communication, financial management and failure management skills that could make them become successful entrepreneurs. The study therefore recommends that Business Education students should make judicious use of the failure management skills possessed to establish their own entrepreneurial outfits and nurture them to maturity after graduation, among others.